PETA PEMIKIRAN HUKUM ISLAM DI INDONESIA - Ahwan Fanani (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2009)
The development of the thought of Islamic law in Indonesia during both pre and post-independence has been experiencing the dynamics, that is proper to have attention from academicians. The development of the thought of Islamic law could not be separated from two factors. Firstly, the development of the thought of Islamic law in the Islamic world is the result of the emergence of international issues such. as human rights, the equality of gender, pluralism, and democracy. Secondly, the contact between Indonesian Muslim intellectuals and other Muslim ones all over the· world. Such intellectual networks have been proven since long time ago to become a connecting point between the development of Islam in the Archipelago and that of other muslim world.